2023
DOI: 10.7759/cureus.34578
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Dementia Knowledge and Its Associated Factors Among Health College Students in Saudi Arabia

Abstract: BackgroundDementia is a public health concern and the main cause of impairment and dependency among the elderly worldwide. It is characterized by a progressive decline in cognition, memory, and all domains of quality of life with preserving the level of consciousness. Accurate measurement of dementia knowledge among future health professionals is required to improve targeted educational initiatives and supportive care of patients. This study aimed to assess knowledge of dementia and its associated factors amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Notably, our findings align with previous research from Saudi Arabia and nearby countries, collectively underscoring significant knowledge deficits related to dementia among healthcare professionals in the region. Aldharman et al reported a mean knowledge score of only 13.68 out of 25 among health college students in Saudi Arabia [ 11 ]. Similarly, Al-Awad et al found that while primary care physicians had a positive attitude toward dementia care, their mean knowledge score was a suboptimal 36.4 out of 50 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, our findings align with previous research from Saudi Arabia and nearby countries, collectively underscoring significant knowledge deficits related to dementia among healthcare professionals in the region. Aldharman et al reported a mean knowledge score of only 13.68 out of 25 among health college students in Saudi Arabia [ 11 ]. Similarly, Al-Awad et al found that while primary care physicians had a positive attitude toward dementia care, their mean knowledge score was a suboptimal 36.4 out of 50 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aldharman et al reported that the majority of the participants demonstrated a poor level of knowledge about dementia. The mean knowledge score was 13.68 ± 3.18 (on a scale of 25) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a systemic review showed that there was a greater incidence in Latin America (8.5%) and a noticeably lower incidence in the four sub-Saharan African regions (2-4%) [11]. Similarly, a crosssectional study from Saudi Arabia that included 1613 participants showed that 16.6% of older individuals were suffering from dementia [6].…”
Section: Review Prevalence Of Dementiamentioning
confidence: 99%
“…However, Alzheimer's disease (AD) is the underlying etiology in approximately 70% of all cases [5]. Other causes of dementia include Lewy body disease, traumatic brain injury, vascular disease, and frontotemporal lobar degeneration [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation